Respuesta :

9514 1404 393

Answer:

  (b)  x = 3, y = 2

Step-by-step explanation:

In order for the triangles to be congruent by the HL theorem, the hypotenuses must be congruent:

  3y = x+3

and the corresponding legs must be congruent:

  y +1 = x

__

We can solve this set of equations by substituting for x:

  3y = (y +1) +3

  2y = 4 . . . . . . . .subtract y

  y = 2 . . . . . . . . .divide by 2

  2+1 = x = 3 . . . substitute for y in the equation for x

The solution is (x, y) = (3, 2).